How do Research Ethics Committee Members Respond to Hypothetical Studies with Children? Results from the MESSI Study. (July 2022) - Taplin, Stephanie; Chalmers, Jenny; Brown, Judith; Moore, Tim; Graham, Anne; McArthur, Morag
Hypothetical scenarios were used to assess the influence of the sensitivity of the study topic, payments, and study methods on research ethics committee (HREC) members' approval of social research studies involving children. A total of 183 Australian HREC members completed an online survey. The higher the perceived sensitivity of the study topic, the less likely the study would be approved by an HREC member. HREC members were most likely to approve each of the hypothetical studies if no payment was offered. Payment was the most common reason for not approving the low risk studies, while risks were the most common reasons for not approving the more sensitive studies. Face-to-face interviews conducted at home with children elicited substantially higher rates of approval from HREC members with more sensitive study topics. Both HRECs and researchers may benefit from additional guidance on managing risks and payments for children and young people in research.